Anaphylaxis with clonal mast cells in normal looking skin – a new entity?. Issue 7 (22nd May 2015) - Bretterklieber, A.; Beham‐Schmid, C.; Sturm, G. J.; Berghold, A.; Brezinschek, R.; Aberer, W.; Aberer, E.
Abstract Background Patients with elevated basal tryptase (sBT) >15 μg/l and anaphylaxis may have an underlying mastocytosis. A monoclonal mast cell activation syndrome with aberrant mast cells (MC) at extracutaneous sites has been described in patients with severe hypotension or anaphylaxis. Methods As MC in patients with elevated sBT might be altered in the skin as well, we studied MC in normal neck skin in anaphylaxis and urticaria patients with elevated sBT. Results A mean of 93.1 (SD 19.1) MC/mm² was counted in normal neck skin in 14 patients with anaphylaxis, 84.0 (SD 13.6) in seven patients with urticaria, 142.0 (SD 24.0) in two patients with eczema, 124.4 (SD 43.2) in five patients with systemic mastocytosis (SM) in comparison with autopsy skin (39.1 MC/mm², SD 12.4). In five of 14 (35.7%) of the anaphylaxis and three of five (60%) SM patients more than 25% of MC were spindle shaped and expressed CD25 antigen. Conclusions We could show for the first time that the normal skin can harbour clonal MC in anaphylaxis patients. Analogous to the criteria for mastocytosis, we suggest a skin score criteria including an elevated number of MC, spindle shape, CD25 expression, c‐Kit mutation and sBT values >20 μg/l. In patients with anaphylaxis and elevated sBT, skin should be biopsied and, as with the approach for mastocytosis diagnosis in the bone marrow, MC should be analysed for their number, clonality and c‐Kit mutation. This approach should be confirmed in further studies. Patients with aberrant skin MC should be handled as mastocytosis patients.